The change of bacterial community structure helped Salvia miltiorrhiza alleviate the pressure of drought stress - Wang, Hai; Wu, Chen; Li, Xiaoyu; Jia, Hongmei; Yan, Zhuyun (Frontiers in Plant Science, 2025)
IntroductionDrought stress poses a significant threat to plant growth and development, thereby adversely impacting agricultural productivity and ecosystem stability. In recent years, increasing attention has been given to plant–microorganism interactions as a promising strategy to enhance plant resistance to abiotic stresses.MethodsIn this study, we evaluated the effects of microbial inoculation on the growth, photosynthetic performance, nutrient uptake, and root morphology of Salvia miltiorrhiza under drought stress. Microbial community composition was also analyzed to explore the interaction between drought stress and rhizosphere microbiota.ResultsOur results demonstrated that microbial inoculation significantly alleviated the adverse effects of drought stress on S. miltiorrhiza. Inoculated plants exhibited a 3.61-fold increase in biomass compared to the uninoculated controls. Chlorophyll content increased by approximately 85.45%, while nitrogen and potassium contents rose by 27.77% and 33.27%, respectively. Furthermore, microbial inoculation improved root system architecture. Drought stress altered the rhizosphere microbial community, with the relative abundance of Enterobacteriaceae increasing by 5.50% and Brucellaceae decreasing by 2.76%.DiscussionThese findings suggest that microorganisms can enhance plant drought resistance through multiple mechanisms, including the promotion of growth, nutrient absorption, and root development, as well as modulation of microbial community structure. This study provides a theoretical foundation and practical insights for the development of microbial-based strategies to improve plant resilience under drought conditions.